The effect of attachment types and implant level on the stress distribution in a mandibular overdenture: a 3D Finite Element Analysis - Aalaei, Shima; Abedi, Paria; Niknami, Sahar; Taghavi , Farnoosh; Taghavi Damghani, Farnaz (Brazilian Dental Science, 2022)
Objective: The objective of this study was to evaluate the stress distribution in bone-surrounding implants placedin different levels in a mandibular overdenture. Material and Methods: A Computerized Tomography (CT) scanof an edentulous mandible was used to generate the models. Two implants with an internal connection wereplaced perpendicular to the occlusal plane in the Canine sites of the mandible. The implant in the left side wasplaced 1mm higher than the other side. Dolder bar and ball attachments were designed. Loading was performedby clenching the teeth with reconstruction of the muscles. In the anterior loading condition, force was appliedto the central incisors and in the posterior loading conditions, it was applied to the molars and premolars. Thenthe Maximum Principal Stresses in the peri implant bone was evaluated with finite element analysis. Results:In both models, the highest stress values were recorded in the cortical bone surrounding the higher implantexcept in the ball model with unilateral load application on the right side (64.7 MPa). In almost all loadingconditions the stress value differences in models with bar and ball attachments were low. Only in the anteriorloading condition, the stress magnitude was higher in two implants of the ball model (60.5 MPa in the left sideand 21 MPa in the right side) compared to the bar model (54.5 MPa in the left side and 17.5 MPa in the rightside). Conclusion: The stress concentration did not affected considerably by the attachment system. High stressvalues were found adjacent the implant with a higher level. To reduce the amount of stress, bilateral balanceocclusion should be considered.KEYWORDSStress; Finite element analysis; Overdenture; Dental implants.